Security Risks and Protection in Online Learning: A Survey - Chen, Yong; He, Wu (International Review of Research in Open and Distributed Learning, 2013)
This paper describes a survey of online learning which attempts to determine online learning providers’ awareness of potential security risks and the protection measures that will diminish them. The authors use a combination of two methods: blog mining and a traditional literature search. The findings indicate that, while scholars have identified diverse security risks and have proposed solutions to mitigate the security threats in online learning, bloggers have not discussed security in online learning with great frequency. The differences shown in the survey results generated by the two different methods confirm that online learning providers and practitioners have not considered security as a top priority. The paper also discusses the next generation of an online learning system: a safer personal learning environment which requires a one-stop solution for authentication, assures the security of online assessments, and balances security and usability.